Spectrophotometric Determination of Magnesium(II) with 3-Hydroxy-3-m-Tolyl-1-p-Nitrophenyltriazene - Maroo, Usha; Maroo, Pradeep; Sharma, Kavita; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
3-Hydroxy-3-m-tolyl-1-p-nitrophenyltriazene has been used for the spectrophotometric determination of Mg(II). Magnesium forms a 1 : 2 (Mg : R) acetone soluble, cherry colour, complex with the reagent. The complex shows maximum absorbance at 530 nm. At working wavelength 560 nm, ε = 11,500 L mole–1 cm–1. For constant maximum colour development Mg : R was 1 : 6 and pH was between 10.4-10.8. Values of molar absorptivity, Sandell's sensitivity, stability constant (log β) and free energy of formation were found to be 11,500 L mole–1 cm–1, 0.21 ng/cm2 ,11.00 and -15.101 kca/mole respectively. Beer's law is obeyed in the entire concentration range studied, i.e., 1.0 x 10–6 M to 6.0 X 10–6 M. It was possible to determine magnesium (0.12 ppm) in presence of two-fold molar excess of ninteeen cations and anions.